The Effect of Level and source of Poultry By-Product Meal as a Promising Protein Source on the Sustainability of Aquaculture Biomass Production of (Oreochromis Niloticus) in KSA - Raad, Suad; Shafi, Manal (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2023)
Fish meal (FM) is an essential product as a primary protein source in the fish feed industry. Due to the expensive price of FM and the negative impact of its high consumption on the environment, alternative protein sources for FM were necessary to be tested. Poultry by-Product meal (PBPM) is a high quality and low-cost protein source. In this study, FM was partially and completely replaced by PBPM in Nile tilapia fingerlings (Oreochromis niloticus) diet to study its effect on biomass performance and nutrient utilization. Six formulas were prepared to replace FM protein with PBPM protein: Maram feed as a commercial control (CC), feed, the experimental control (EC) 0% PBPM, (C3) 32% PBPM, (C4) 67% PBPM, (C5) 100% PBPM-Saudi Radwa Feed company (SRFC), and (C6) 100% PBPM-Con. The study period was extended for 56 days in outdoor ponds. Nile tilapia fingerlings were fed three times daily (initial average weight = 41 g). Final survival ranged between 97% and 72% in all diet treatments and final gain was (41.32g – 14.73g). However, the gain of C4 (41.32) was higher than in the controls CC (38.24) and EC (40.69) also, feed conversion ratios FCR (1.21– 4.29). The best results of growth performance and nutrient utilization were for C4 (67% PBPM). The results of this study showed that poultry by-product meal is a great alternative protein source up to 67% of the fish meal for fish meal for the feeding of Nile tilapia fingerlings.